1996
DOI: 10.1074/jbc.271.36.22189
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the RNA Polymerase I and III Transcription Systems in Response to Growth Conditions

Abstract: To better understand the mechanisms that regulate stable RNA synthesis, we have analyzed the RNA polymerase I and III transcriptional activities of extracts isolated from cells propagated under a variety of conditions. Under balanced growth conditions the levels of both RNA polymerase I-and III-specific transcription increased proportionally with growth rate. Upon nutritional starvation, RNA polymerase I transcription rapidly declined, followed by 5 S rDNA and eventually tDNA transcription. Transcriptional act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…Gcn4p thus appears to be a key regulatory protein in the global remodeling of RNA Pol II-dependent genome expression elicited by diverse signals of starvation and stress. Several environmentally stressful conditions, such as nutrient limitation, secretion defects, and treatment with DNA-damaging agents, are known to severely downregulate RNA Pol III-dependent transcription in yeast (9,12,21,34,49,52,58). The reduction in the level of initiator tRNA Met resulting from such perturbations might contribute to GCN4 translational activation and the consequent, genome-wide reprogramming of RNA Pol II-dependent transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gcn4p thus appears to be a key regulatory protein in the global remodeling of RNA Pol II-dependent genome expression elicited by diverse signals of starvation and stress. Several environmentally stressful conditions, such as nutrient limitation, secretion defects, and treatment with DNA-damaging agents, are known to severely downregulate RNA Pol III-dependent transcription in yeast (9,12,21,34,49,52,58). The reduction in the level of initiator tRNA Met resulting from such perturbations might contribute to GCN4 translational activation and the consequent, genome-wide reprogramming of RNA Pol II-dependent transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The triplication of the transcriptional machinery may provide a selective advantage to the eukaryotic cell, compared to the unique bacterial and archaeal RNA polymerases, by allowing independent or coordinated regulations of gene expression in response to environmental changes. Previous studies both in yeast and in higher eukaryotes have shown that Pol III transcription is coordinately regulated with Pol I transcription under many circumstances, e.g., upon nitrogen starvation or in response to a nutritional upshift (6,9,53,58). Under other conditions, the regulatory pathways of Pol I and Pol III transcription are uncoupled.…”
mentioning
confidence: 99%
“…In fact, the main evidence for coordinated control of the transcriptional synthesis of rRNA, ribosomal protein mRNAs, and tRNAs is that blocking protein secretion inhibits these three processes in a way that requires protein kinase C (19). On the other hand, rRNA and tRNA synthesis can be uncoupled under physiological conditions, such as amino acid starvation (6,23). Even under balanced growth conditions, the cellular levels of tRNAs and rRNAs are roughly but not strictly constant, since rRNAs are more strongly affected than tRNAs in slow-growing cells (15,32,37).…”
Section: Discussionmentioning
confidence: 99%
“…We then investigated the relationships between gene activity and occupancy by the Pol III machinery. Pol III transcription is high in rich medium, and repressed during nutrient deprivation (17). Accordingly, we subjected yeast cultures bearing tagged Pol III machinery to the following regimen: logarithmic growth (nutrient replete), nutrient deprivation, and nutrient reintroduction.…”
Section: B-e)mentioning
confidence: 99%
“…Several conditions related to nutrient deprivation and cell stress can lead to a rapid and͞or dramatic reduction in Pol III transcription (17)(18)(19)(20). Stress conditions are relayed to the Pol III machinery by various signaling pathways, including those mediated by CK2 and Pkc1 (19)(20)(21).…”
mentioning
confidence: 99%